Biotreatment of AL-KARAMA Teaching Hospital Wastewater Using Aerobic Packed Bed (Baghdad Science Journal, 2013)
This study is aimed to use the aerobic packed bed in biotreatment of the wastewater which is discharge from AL-KARAMA teaching hospital in Baghdad. The performance of packed-bed treatment method was examined for elimination of the organic compounds from wastewater under aerobic conditions. In this research different parameters were studied. They were: inoculums concentration, circulation rate of wastewater through the bed, packing type and the temperature. Results showed that the system efficiently removed about 82% of the chemical oxygen demand (COD) and 80% of the Biological oxygen demand (BOD). Percent reduction in turbidity was about 92% and reduction in nitrate concentration was about 87%. It was found that best performance of the packed bed method was obtained at temperature of 37 oC, circulation rate of 10 L/min and inoculums concentration of 3%.